2021
DOI: 10.29303/jpm.v16i3.2595
|View full text |Cite
|
Sign up to set email alerts
|

Anacardic Acid Isolation from Cashew Seed Skin

Abstract: Research on the isolation of anacardic acid compounds from cashew nut shells has been carried out. This study aims to develop a method of isolating anacardic acid compounds from cashew nut shells in an easier way but still produces compounds that remain pure. In this study isolation and identification of anacardic acid compounds contained in CNSL was carried out. The results of anacardic acid isolation contained in CNSL in the form of a thick brown extract that has a characteristic dark odor. Anacardic acid wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…The activity test of flavonoid compounds from mango leaf extract as anti-bacterial showed that mango leaf flavonoid isolates produced a larger diameter of inhibition zone than mango leaf ethanol extract against Escherichia coli and Staphylococcus aureus bacteria [15], so it was concluded that flavonoid compounds play an active role in inhibiting bacterial growth. In another study, the anti-bacterial activity of Syzygium polyanthum fruit which contains flavonoids, alkaloids, terpenoids, tannins, and saponins, can inhibit the growth of Escherichia coli bacteria [16].…”
Section: Total Microbesmentioning
confidence: 99%
“…The activity test of flavonoid compounds from mango leaf extract as anti-bacterial showed that mango leaf flavonoid isolates produced a larger diameter of inhibition zone than mango leaf ethanol extract against Escherichia coli and Staphylococcus aureus bacteria [15], so it was concluded that flavonoid compounds play an active role in inhibiting bacterial growth. In another study, the anti-bacterial activity of Syzygium polyanthum fruit which contains flavonoids, alkaloids, terpenoids, tannins, and saponins, can inhibit the growth of Escherichia coli bacteria [16].…”
Section: Total Microbesmentioning
confidence: 99%